Exercise Limitation in Children and Adolescents With Severe Refractory Asthma: A Lack of Asthma Control? - Faleiro, Rita C.; Mancuzo, Eliane V.; Lanza, Fernanda C.; Queiroz, Mônica V. N. P.; de Oliveira, Luciano F. L.; Ganem, Vinicius O.; Lasmar, Laura B. (Frontiers in Physiology, 2021)
Background: Patients with severe refractory asthma (SRA), even when using high doses of multiple controller medications in a regular and appropriate way, can have persistent complaints of exercise limitation. Methods: This was a cross-sectional study involving patients with SRA (treated with ≥ 800 µg of budesonide or equivalent, with ≥ 80% adherence, appropriate inhaler technique, and comorbidities treated), who presented no signs of a lack of asthma control other than exercise limitation. We also evaluated healthy controls, matched to the patients for sex, age, and body mass index. All participants underwent cardiopulmonary exercise testing (CPET) on a cycle ergometer, maximum exertion being defined as ≥ 85% of the predicted heart rate, with a respiratory exchange ratio ≥ 1.0 for children and ≥ 1.1 for adolescents. Physical deconditioning was defined as oxygen uptake (VO2) < 80% of predicted at peak exercise, without cardiac impairment or ventilatory limitation. Exercise-induced bronchoconstriction (EIB) was defined as a forced expiratory volume in one second ≥ 10% lower than the baseline value at 5, 10, 20, and 30 minutes after CPET. Results: We evaluated 20 patients with SRA and 19 controls. In the sample as a whole, the mean age was 12.9 ± 0.4 years. The CPET was considered maximal in all participants. In terms of the peak VO2 (VO2peak), there was no significant difference between the patients and controls, (P = .10). Among the patients, we observed isolated EIB in 30%, isolated physical deconditioning in 25%, physical deconditioning accompanied by EIB in 25%, and exercise-induced symptoms not supported by the CPET data in 15%. Conclusions and Clinical Relevance: Physical deconditioning, alone or accompanied by EIB, was the determining factor in reducing exercise tolerance in patients with SRA, and was not therefore found to be associated with a lack of asthma control.